Synthesis of novel hydrated ferric oxide biochar nanohybrids for efficient arsenic removal from wastewater - Zhu, Tong; Zhang, Yun; Chen, Yu; Liu, Jun-Liang; Song, Xiao-Li (Rare metals, 2022)
Hydrated ferric oxide (HFO) has high adsorption efficiency for As(III). However, its high self-aggregation usually reduces the efficiency and limits the scaled-up application. Herein, biochar (BC), with large surface area and amounts of surface functional groups was used to tune the loading and distribution of HFO to prepare an efficient adsorbent (HFO/BC) via in-situ synthesis method. The influence of the mass ratio of iron salt to BC on HFO/BC morphology was investigated, and the mechanism was discussed. The results showed that novel HFO was formed and distributed uniformly on the surface of BC when the mass ratio of iron salt to BC was 5:1. The adsorption kinetics and isotherms studies show that the novel HFO/BC (5:1) composite can fast treat As(III) with a high adsorption capacity of 104.55 mg·g −1 , indicating that it is a potential material for removing arsenic from polluted water. Graphic abstract